Aspects of the biology of two inshore sparid fishes (Diplodus sargus capensis and Diplodus cervinus hottentotus) off the south-east coast of South Africa - Mann, Bruce Quintin (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1992)
The blacktail, Diplodus sargus capensis and the zebra, Diplodus cervinus hottentotus, sparid fishes endemic to South Africa, are important components of the recreational shore-fishery. To provide a basis for the management of these fish, aspects of the biology of both species were investigated in the Tsitsikamma National Park (TNP). In particular, the role of the TNP was evaluated as a management option for the conservation of both species. Examination of stomach contents showed that juveniles of both species fed predominantly on amphipods, polychaetes and harpacticoid copepods. Adult !h. sargus were omnivorous and fed opportunistically on a wide variety of reef associated invertebrates and algae including echinoids, polychaetes, anthozoans, ascidians and rhodophytes. The diet of adult D. cervinus was more specialized with a preference shown for polychaetes and amphipods. Seasonal differences were apparent in the diets of both species where considerably more amphipods were consumed in winter than in summer. Feeding requirements of both species were reflected in their habitat preferences. Visual underwater assessment revealed that both species were most abundant on turbulent inshore reefs (1-10m). !h. sargus were observed over a wide variety of reef associated habitats. In the literature they have also been recorded in the surf zone of sandy beaches and in the lower reaches of estuaries. !h. cervinus, on the other hand, were more specific in their habitat requirements and were observed in greatest abundance on inshore reefs, often in close association with caves or overhangs. A comparison between the relative abundance and size structure of both species in the TNP with that of an exploited area immediately adjacent to the reserve, showed no significant differences. This was attributed to the low level of exploitation by rock-and-surf anglers occurring in the exploited study area, as well as the possibility of seeding of eggs and larvae, or emigration of adults from the TNP. An investigation of the reproductive biology of both fish showed that !h. sargus had an extended summer spawning season while in !h. cervi nus it was more restricted. Detailed histological examination of gonadal development showed that !h. sarqus were dygynous with partial protandry occuring in the male population. ~ cervinus were shown to be rudimentary hermaphrodites. Size at 50% maturity in ~ sargus and ~ cervinus was determined at 225 and 285mm fork length respectively, corresponding to ages of 4 and 6 years. An age and growth study based on the examination of sectioned otoliths showed that both species were slow growing capable of reaching ages in excess of 20 years. Growth in ~ sargus and ~ cervinus was described by the von Bertalanffy growth equations: L(t) = 309.44(1-e-0 . 247[t+l. 048 l) and L(t) = 396.85(1-e-0.146[t+2.148J) respectively. Life history characteristics of D. sargus and D. cervinus including slow growth, late maturation and occupation of a localised, demersal habitat showed that both species were vulnerable to the effects of over-fishing. Due to the present increase in the number of participants and the decrease in catch per unit effort in the recreational shore-fishery, more stringent management recommendations were proposed to ensure the adequate protection of both species. These included an increased minimum size limit and a decreased bag limit for both species. Based on the residency shown by both species and their high relative abundance in the TNP, marine reserves were considered to be a valuable addition to the suite of management options available for the conservation of these species . In this respect the reserve provided both protection for the spawner stock as well as the potential to seed adjacent areas.
Keywords: Sparidae; Diplodus